Tinjauan Hukum Pidana Islam Dan Hukum Pidana Positif Terhadap Pemerasan Yang Bermotif Penyebaran Video Syur Di Media Sosial - Alfikri, Maulianda; Zulkarnain, Zulkarnain (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2024)
The spread of indecent or inappropriate content through social media has become a serious problem in this digital era. This can have negative impacts, especially when the content concerns a person's personal life and has caused suffering and psychological suffering for the victim. In response to this problem, it is important to review Islamic criminal law and positive criminal law regarding the protection of individuals who become victims of actors who are motivated to spread pornographic videos on social media. This study aims to analyze and compare the views of Islamic criminal law and positive criminal law regarding acts of extortion motivated by the spread of pornographic videos on social media. The existence of criminal law in Islam and positive law each brings a unique approach to the protection of individuals who are victims of such acts. Through a comparative approach, it is hoped that similarities and differences in the protection of individuals in the two legal systems can be found. The research method used in this study is the analytical descriptive method. Data were collected through a literature study covering sources of Islamic law such as the Qur'an, hadith, and Islamic studies, as well as sources of positive law such as laws and related government regulations. The results of this study indicate that both legal systems have provisions that prohibit and criminalize the act of spreading pornographic videos on social media. However, there are differences in the approaches and sanctions imposed, as well as concepts of punishment that may differ in the context of Islamic criminal law and positive criminal law. Punishment in Islam is often based on the concepts of ta'zir, qisas, and diyat, while in positive law it is often based on criminal sanctions regulated in legislation. This study contributes to broadening the understanding of the protection of individuals who are victims of the spread of inappropriate content on social media, and provides insight into the similarities and differences between Islamic criminal law and positive criminal law in the context of blackmail motivated by the spread of pornographic videos. In addition, the results of this study can also be a basis for further research in an effort to improve regulations related to the protection of individuals in the digital context in the future. [Penyebaran konten tidak senonoh atau tidak pantas melalui media sosial telah menjadi permasalahan serius di era digital ini. Hal ini dapat berdampak negatif, terutama ketika konten tersebut menyangkut kehidupan pribadi seseorang dan telah menimbulkan penderitaan dan penderitaan psikologis bagi korban. Sebagai respons terhadap permasalahan ini, penting untuk meninjau hukum pidana Islam dan hukum pidana positif terkait perlindungan terhadap individu yang menjadi korban pemeran yang bermotif penyebaran video syur di media sosial. Studi ini bertujuan untuk menganalisis dan membandingkan pandangan hukum pidana Islam dan hukum pidana positif mengenai tindakan pemerasan yang bermotif penyebaran video syur di media sosial. Keberadaan hukum pidana dalam Islam dan hukum positif masing-masing membawa pendekatan yang unik terhadap perlindungan terhadap individu yang menjadi korban dari tindakan tersebut. Melalui pendekatan perbandingan, diharapkan dapat ditemukan kesamaan dan perbedaan dalam perlindungan terhadap individu di dua sistem hukum tersebut. Metode penelitian yang digunakan dalam studi ini adalah metode deskriptif analitis. Data dikumpulkan melalui studi pustaka yang meliputi sumber hukum Islam seperti Al-Qur’an, hadis, dan kajian-kajian Islam, serta sumber hukum positif seperti undang-undang dan peraturan pemerintah terkait. Hasil dari penelitian ini menunjukkan bahwa kedua sistem hukum memiliki ketentuan yang melarang dan mengkriminalisasi tindakan penyebaran video syur di media sosial. Namun, terdapat perbedaan dalam pendekatan dan sanksi yang diberlakukan, serta konsep-konsep hukuman yang mungkin berbeda dalam konteks hukum pidana Islam dan hukum pidana positif. Hukuman dalam Islam sering kali didasarkan pada konsep ta'zir, qisas, dan diyat, sedangkan dalam hukum positif seringkali didasarkan pada sanksi pidana yang diatur dalam perundang-undangan. Studi ini memberikan kontribusi dalam memperluas pemahaman mengenai perlindungan terhadap individu yang menjadi korban dari penyebaran konten tidak pantas di media sosial, serta memberikan wawasan tentang kesamaan dan perbedaan antara hukum pidana Islam dan hukum pidana positif dalam konteks pemerasan yang bermotif penyebaran video syur. Selain itu, hasil dari studi ini juga dapat menjadi landasan bagi penelitian lebih lanjut dalam upaya penyempurnaan regulasi terkait perlindungan individu dalam konteks digital di masa yang akan datang].